Phantasie und Akribie Haggada und Halacha im Judentum und die christliche Predigt - Deeg, Alexander 1972- (2007)
Fantasy and Meticulousness: Haggada and Halacha in Judaism and the Christian Sermon. The article deals with these Jewish traditions and ways of interpreting the Holy Scriptures, and explores what Christian preaching can learn from them.
Aufsatz
Keywords: Aggadah; Homiletik; Halacha